1993
DOI: 10.1080/09593339309385334
|View full text |Cite
|
Sign up to set email alerts
|

Uranium in sediments from the Magela Creek catchment, northern territory, Australia

Abstract: The 'fine silt and clay' fraction of sediments from various tropical billabongs (permanent waterbodies) in the Magela Creek catchment, Northern Australia, were analysed for uranium by delayed neutron activation analysis. Sediment samples were from a range of billabong types: backflow (4 samples), channel (2 samples) and floodplain (5 samples) and were sampled and prepared for analysis as described by Thomas and Hart (1). Uranium concentration data from this study are compared with previously reported uranium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…), the findings presented here point towards the importance of internal mechanisms and feedbacks within the eco‐hydro‐geomorphic system with environmental implications on multiple timescales. Firstly, downstream of mine sites, pollutants such as heavy metals or U are dominantly associated to fine‐grained floodplain sediments (Noller and Hart, ; Taylor, ). Even after decades of stability following site rehabilitation, excavation of these sediments through incision and bank erosion related to knickpoint passage may thus lead to the abrupt liberation and downstream transmission of contaminated sediment and water (East et al , ; Taylor, ; Caitcheon et al , ), demonstrating the need for more integrated bio‐geomorphological perspectives towards a more comprehensive understanding of pollution cycles in general (Mudd and Patterson, ).…”
Section: Discussion: Wangi Creek As a Tropical Cut‐and‐fill River‐flomentioning
confidence: 99%
“…), the findings presented here point towards the importance of internal mechanisms and feedbacks within the eco‐hydro‐geomorphic system with environmental implications on multiple timescales. Firstly, downstream of mine sites, pollutants such as heavy metals or U are dominantly associated to fine‐grained floodplain sediments (Noller and Hart, ; Taylor, ). Even after decades of stability following site rehabilitation, excavation of these sediments through incision and bank erosion related to knickpoint passage may thus lead to the abrupt liberation and downstream transmission of contaminated sediment and water (East et al , ; Taylor, ; Caitcheon et al , ), demonstrating the need for more integrated bio‐geomorphological perspectives towards a more comprehensive understanding of pollution cycles in general (Mudd and Patterson, ).…”
Section: Discussion: Wangi Creek As a Tropical Cut‐and‐fill River‐flomentioning
confidence: 99%
“…This assumption was necessitated by the limited organic carbon data available for groundwater, surface water and soil at the site. However, soil sampling (SLR 2018) and sediment sampling (Noller & Hart 1993) have indicated that organic matter would not likely be a limiting factor for the potential formation of ASS in areas where waterlogging of soils and sediments may occur. This is consistent with the understanding that billabongs and wetlands generally have an abundant supply of carbon from decomposing plant material and/or algae (Baldwin 2017a).…”
Section: Premisementioning
confidence: 99%
“…As it migrates through the environment it can become 'fixed' in humic rich areas such as peat bogs, 2 and billabongs. 3,4 Typical levels of uranium found in natural waters range from 0.1 to 7 ng ml À1 for streams and 2 to 4 ng ml À1 in seawater. 5 However, these levels can be elevated due to input from anthropogenic sources such as nuclear power plants and radioactive waste repositories.…”
Section: Introductionmentioning
confidence: 99%